Bytelearn - cat image with glassesAI tutor

Welcome to Bytelearn!

Let’s check out your problem:

Rewrite the function by completing the square.

{:[f(x)=x^(2)-16 x+76],[f(x)=(x+◻)^(2)+◻]:}

Rewrite the function by completing the square.\newlinef(x)=x216x+76 f(x) = x^2 - 16x + 76 \newlinef(x)=(x+)2+ f(x) = (x + \square)^2 + \square

Full solution

Q. Rewrite the function by completing the square.\newlinef(x)=x216x+76 f(x) = x^2 - 16x + 76 \newlinef(x)=(x+)2+ f(x) = (x + \square)^2 + \square
  1. Rewriting the function: Now we rewrite the function by factoring the perfect square trinomial and combining the constants.\newlinef(x)=(x8)2+7664f(x) = (x - 8)^2 + 76 - 64\newlinef(x)=(x8)2+12f(x) = (x - 8)^2 + 12
  2. Completing the square: We have successfully rewritten the function by completing the square. The function is now in the form f(x)=(xh)2+kf(x) = (x - h)^2 + k, where hh and kk are constants.\newlineThe completed square form of the function is f(x)=(x8)2+12f(x) = (x - 8)^2 + 12.

More problems from Solve a quadratic equation by completing the square